A Short Review of Pediatric Respiratory Presentation in COVID-19 - Eshghi, Alireza; Hoseiny Nejad, Nasrin (Journal of Pediatric Nephrology, 2020)
As the novel coronavirus infection has involved the whole world, and children are the victims as adults, and yet there are many obscure points about this global problem, this review study is aimed to evaluate its clinical and paraclinical presentations particularly in young ages. In this review, we performed using PubMed and Google scholar database and motor of search. The meta-analysis, reviews and case series done on COVID-19 patients especially on youngsters under 18 years, were considered. Fever and cough are prevalent in children involvement like adults. Pneumonia is the most common complication in novel coronavirus. Children have better prognosis and severe disease in this group is rare. Bilateral patchy densities and ground-glass opacities are prevalent in chest CT scan of pediatric COVID-19. Although there are some differences between pediatric and adult COVID-19, similarities between respiratory signs and symptoms in these two groups are prominent. Keywords: COVID-19; SARS-cov-2; Coronavirus; Children.